Cation/macromolecule interaction in alkaline cellulose solution characterized with pulsed field-gradient spin-echo NMR spectroscopy. Issue 11 (6th March 2017) - Wang, Sen; Sun, Peng; Zhang, Rongrong; Lu, Ang; Liu, Maili; Zhang, Lina
Abstract : Using an alternative to the traditional method of 1 H diffusometry, the interaction of cations with the cellulose macromolecule is investigated with facileness, accuracy and precision. Abstract : As a breakthrough to the traditional 1 H diffusometry, the interaction of cations with cellulose is investigated via 7 Li and 23 Na PFG-SE NMR. The diffusion coefficient of Li + decreases more than that of Na + with the addition of cellulose, which indicates a stronger binding of LiOH with the macromolecule. Therefore, a new, facile, accurate and repeatable method to characterize ion/polymer interactions is established.